(untitled) (PIONIR: JURNAL PENDIDIKAN, 2020)
The development of children at the elementary age must be guided and nurtured, this development must be maintained together by the family / parents, teachers / schools and the community. If this does not go well, there will be a lot of distortion phenomena by elementary school age children, such as smoking, bullying, stealing, fighting and the most concern is that there is free sex and drugs. Based on this, it is necessary to know that the moral development of children of conscious age really needs to be known and understood. This study aims to analyze the religious and moral development of elementary age children. Followed by examining information to describe the stages of moral and religious development of children, examining how the characteristics shown by children correspond to their developmental stages. This research is a literature study, in the form of research whose objects are literature works, namely scientific journals, books, articles. The results showed that the stages of children’s moral and religious development have certain characteristics and are highly dependent on environmental factors, environmental factors are expected to support, remind, supervise, guide and set good examples based on religious morals, namely the Al-Qur’an and Hadith.